Developing a Bintan Island Fairy Tale Book to Enhance Early Childhood Social-Emotional Development - Awlya Nanda Awhar; Chandra Apriyansyah; Nita Priyanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the factual conditions of social-emotional learning for children aged 5–6 years, develop a storybook based on the local wisdom of Bintan Island, test the feasibility of the product, and evaluate its effectiveness. The study used the Research and Development method with the 4D model (Define, Design, Develop, Disseminate), which was implemented at YKPP Tanjung Uban Kindergarten, Bintan Regency, in March–May 2025. The subjects of the study were 24 children in group B. Data were collected through observation, interviews, documentation, and expert validation sheets; then analyzed descriptively, thematically, and gain score. The results showed that 62.5% of children had not achieved optimal social-emotional development, with self-control as the lowest indicator (47.9%). The product developed was a 20-page A4 landscape format storybook with five marine biota characters from Bintan Island and a teacher's guide. The product's feasibility was in the very feasible category with an average of 94.6% (content experts 93.3%; language experts 95.0%; media experts 95.6%). The effectiveness test showed an increase in the average score from 25.75 to 41.25, with a 69.7% gain in the medium category. Qualitative findings also demonstrated the transfer of learning to children's real-life behavior. Therefore, the storybook based on local wisdom from Bintan Island is suitable and effective as a social-emotional learning medium for early childhood.